Anterior chamber changes assessment by Scheimpflug analysis after intravitreal dexamethasone implantation. Issue 1 (January 2022) - Kucukkomurcu, Elvan; Sahin, Tayfun
Purpose: To evaluate structural changes in the anterior chamber and intraocular pressure (IOP) changes following intravitreal dexamethasone implantation. Methods: Forty-two eyes of 42 patients that received intravitreal dexamethasone implant for the management of macular edema secondary to diabetic retinopathy or branch retinal vein occlusion (BRVO) were included in the study. IOP was measured by Goldmann applanation tonometry. Anterior chamber depth (ACD) and iridocorneal angle (ICA) was measured by a Scheimflug camera (Sirius, CSO, Italy) the day before the injection of the dexamethasone implant and on postoperative day 1, first week, and first month. Results: Mean IOP was 15.14 ± 2.77 mmHg before the procedure and, 15.67 ± 3.70 mmHg, 15.86 ± 3.11 mmHg, 16.21 ± 2.75 mmHg on day 1, first week, and first month following intravitreal dexamethasone implantation, respectively. Mean ICA and ACD were significantly higher in pseudophakic eyes compared to phakic eyes. However, there was no statistically significant change in ICA before and after the procedure (on postoperative day 1, first week, and first month) among both phakic and pseudophakic patients ( p = 0.783). Similarly, ACD remained unchanged after the procedure (on postoperative day 1, first week, and first month) compared to the initial measurement ( p = 0.802). Conclusion: This study confirmed that there was an increase in IOP. However, these changes were not accompanied with a change in ACD or ICA.